Percutaneous Microwave Ablation Versus Open Surgical Resection for Colorectal Cancer Liver Metastasis - Zhao, Qinxian; Cheng, Zhigang; Han, Zhiyu; Liu, Fangyi; Yu, Xiaoling; Tan, Xianliang; Han, Bin; Dou, Jianping; Yu, Jie; Liang, Ping (Frontiers in Oncology, 2021)
Purpose To compare the therapeutic outcomes between open surgical resection (OSR) and percutaneous microwave ablation (PMWA) for colorectal liver metastasis (CRLM) ≤3 cm. Methods In this retrospective study, 200 consecutive patients with 306 CRLMs were reviewed. Overall survival (OS), disease-free survival (DFS), local tumour progression (LTP), intrahepatic distant recurrence, and extrahepatic metastasis were analysed to compare the therapeutic efficacy. Cox proportional hazards regression analysis was used to identify the prognostic factors for OS and DFS. Major complications and postoperative hospital stay were also assessed. Result The 1-, 3-, and 5-year OS rates were 91.6%, 64.1%, and 46.3%, respectively, in the PMWA group and 89.7%, 62.4% and 44.7%, respectively, in the OSR group (P=0.839). The 1-, 3-, and 5-year DFS rates were 61.9%, 44.8%, and 41.3%, respectively, in the PMWA group and 58.1%, 24.4%, and 18.3%, respectively, in the OSR group (P =0.066). The two groups had comparable 5-year cumulative rates of intrahepatic distant recurrence (P=0.627) and extrahepatic metastasis (P=0.884). The 5-year cumulative LTP rate was lower in the OSR group than in the PMWA group (P=0.023). The rate of major complications was higher in the OSR group than in the PMWA group (P =0.025), and the length of hospital stay after treatment was shorter in the PMWA group (P<0.001). Conclusion There were no significant differences in OS or DFS between the two groups. PMWA was associated with increased LTP, fewer postoperative days and fewer major complications.